Public environmental literacy through blue economy discourse: A media analysis in North Maluku (2020–2021) - Syamsul Bahri Abd. Rasyid; Misran Misran; Herdin Arie Saputra (Education and Development Research, 2025)
North Maluku is one of the provinces in Indonesia, and two-thirds of its territory is in the ocean. Therefore, further exploration is needed to see how the distribution of discourse in online news media is related to the utilization of marine resources using sustainable principles through the blue economy. This study aims to describe the concept of the blue economy within the framework of sustainable development in North Maluku, with indicators of efficient use of natural resources, empowerment of local resources, zero waste, poverty alleviation, and employment absorption, based on news reporting by online media. The qualitative-descriptive method was used to analyze news from five online news media using NVivo 12 plus software. The results of the study show that: 1) the intensity of news reporting on the blue economy discourse based on indicators is dominated by the indicator of efficient use of natural resources for the Pikiran-rakyat.com, Mongabay.co.id, Kieraha.com, and Kabarpulau.co.id media. In contrast, Kompas.com is more dominated by indicators of the empowerment of local resources. 2) Word frequency analysis on the five online news media found that the keywords related to the blue economy in North Maluku boil down to issues of fisheries and marine management, mangroves, and waste. 3) Meanwhile, the cluster analysis shows that each indicator has a close relationship with different levels of closeness values. From the overall analysis of the news, it is concluded that implementation based on the principles of the blue economy has been carried out on several indicators, although not yet optimal.